Literatura e cinema. Diálogos na era da interatividade - Mestre, Isa (2017)
This paper aims to explore the way as the digital interactive book allow us to think new narrative paths where cinematographic and literary language converge, becoming a single language in the construction of a new hypermediatic narrative. In this context we will present the project “Digital Media: New Scenarios for literature”, a PhD project that aims to recreate a novel on paper to an interactive digital book, for iPad, using textual, sound, audiovisual and interactive languages. We propose to think the hypermedia world as a common platform whereby literature and cinema closely dialogue and unite potential in the construction of a new object that seeks to explore the boundaries of all languages that compose him. This books aims also to enrich the filmic/visual, textual and interactive literacies of the reader.